A frequency domain approach for estimating relative time lag between vibration measurement data. (15th February 2019) - Zhou, H.F.; Yang, M.; Wang, W.D.; Ni, Y.Q.
Highlights: Identify relative time lag inversely from phase angle shift. Find out actual relative time lag by slope of phase angle curve. Fulfill correct identification and avoid false-positive identification. Obtain a conservative estimate using a lower mode. Abstract: The synchronicity of the measurement data at different locations of a structure is essential to structural health monitoring. Sometimes, however, non-synchronicity may occur in them. A frequency domain approach is proposed for the estimation of the relative time lag between vibration measurement data. Making use of the mapping between a relative time lag in the time domain and a phase angle shift in the frequency domain, the relative time lag between either two outputs of a structure is determined by finding a mode where the actual phase angle between them is ideally zero and then calculating the perturbed phase angle that corresponds to the modal frequency of the selected mode. To address the problem of non-uniqueness of solutions, the slope of the phase angle curve is employed to identify the actual relative time lag from a pool of candidates. Extensive validations have been carried out with the use of filed measurement data. Asynchronous acceleration data recorded during a ship-collision of the Jiangyin Bridge were employed to examine its capability to fulfill correct identification of relative time lag. Synchronous acceleration data of the Canton tower under ambient excitations were exploited to test its capability to avoid false-positive identification of relative time lag. The proposed frequency domain approach achieved a satisfactory performance in the identification of relative time lag for both asynchronous and synchronous measurement data.